1, 1‐Diphenylvinylsulfide as a Functional AIEgen Derived from the Aggregation‐Caused‐Quenching Molecule 1, 1‐Diphenylethene through Simple Thioetherification. Issue 6 (30th December 2019) - Wang, Bo‐Wen; Jiang, Kai; Li, Jian‐Xiao; Luo, Shi‐He; Wang, Zhao‐Yang; Jiang, Huan‐Feng
Abstract: An efficient and readily scalable thioetherification between 1, 1‐diphenylethene (DPE) and sodium arylsulfinate was developed for the synthesis of 1, 1‐diphenylvinylsulfide (DPVS) with the yield up to 99 %. The photophysical properties of DPVS show that the introduction of arylsulfenyl groups onto the parent molecule DPE makes DPVS a novel type of aggregation‐induced emission (AIE) luminogen (AIEgen) with large Stoke's shift (up to 188 nm). These DPVS possess AIE properties due to restriction of intramolecular motions (RIM), as demonstrated by crystal structure analysis. Importantly, the AIE performance of DPVS can be applied to sense the nitroaromatic explosive picric acid in aqueous systems through a "turn‐off" response. Abstract : A simple thioetherification between 1, 1‐diphenylethene as an aggregation‐induced emission (AIE)‐imparting unit and sodium sulfinates provides a new route for the conversion of compounds with aggregation‐caused quenching (ACQ) properties into AIE luminogens. This reaction delivers up to 99 % yield under mild conditions without additional oxidant, and gives access to novel trisubstituted‐ethene‐type AIEgens with potential for use in sensing applications.